2020
DOI: 10.1155/2020/8863370
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Vibrio Species from Surface and Drinking Water Sources and Assessment of Biocontrol Potentials of Their Bacteriophages

Abstract: The aim of this study was to characterise Vibrio species of water samples collected from taps, boreholes, and dams in the North West province, South Africa, and assess biocontrol potentials of their bacteriophages. Fifty-seven putative Vibrio isolates were obtained on thiosulfate-citrate-bile-salt-sucrose agar and identified using biochemical tests and species-specific PCRs. Isolates were further characterised based on the presence of virulence factors, susceptibility to eleven antibiotics, and biofilm formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…The aforementioned is of potential health risk to individuals using watershed for recreational, agricultural, and domestic purposes most especially at the downstream of WWTP final effluents discharge points. In some studies from other provinces of South Africa, the isolation of Vibrio harveyi , V. parahaemolyticus , V. cholerae , V. mimicus , and V. vulnificus from tap, borehole, and dam in North West province ( Maje et al, 2020 ) and V. cholerae from four WWTPs located in Gauteng Province ( Dungeni et al, 2010 ) has also been reported. Health risks that an individual using these water resources could be exposed to include gastrointestinal infections caused by V. parahaemolyticus , V. mimicus , and V. fluvialis ; wound infections caused by V. vulnificus and V. harveyi ; cholera caused by V. cholerae ; and cholera-like bloody diarrhea caused by V. fluvialis ( Ramamurthy et al, 1994 ; Igbinosa and Okoh, 2010 ; Jones, 2017 ; Brehm et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned is of potential health risk to individuals using watershed for recreational, agricultural, and domestic purposes most especially at the downstream of WWTP final effluents discharge points. In some studies from other provinces of South Africa, the isolation of Vibrio harveyi , V. parahaemolyticus , V. cholerae , V. mimicus , and V. vulnificus from tap, borehole, and dam in North West province ( Maje et al, 2020 ) and V. cholerae from four WWTPs located in Gauteng Province ( Dungeni et al, 2010 ) has also been reported. Health risks that an individual using these water resources could be exposed to include gastrointestinal infections caused by V. parahaemolyticus , V. mimicus , and V. fluvialis ; wound infections caused by V. vulnificus and V. harveyi ; cholera caused by V. cholerae ; and cholera-like bloody diarrhea caused by V. fluvialis ( Ramamurthy et al, 1994 ; Igbinosa and Okoh, 2010 ; Jones, 2017 ; Brehm et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…2015). This bacterium has been detected in freshwater in some cases (Maje et al . 2020; Silva et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is a seafood-associated and a water-borne foodmediated bacterium (Liu et al 2015). This bacterium has been detected in freshwater in some cases (Maje et al 2020;Silva et al 2018). In addition to the presence of these bacteria, we also detected some Op genera that are closely related to Corynebacterium and Mycobacterium.…”
mentioning
confidence: 99%
“… 115 , 119 , 120 Increasing numbers of antibiotic-resistant virulent Vibrio species are being isolated from the dam, boreholes, and tap water, and the screening of phages that lyse antibiotic-resistant Vibrio species by Maje et al 2020, is essential for safeguarding the biosecurity of water supplies. 121 Aquaculture farmers usually rely on much preventive use of antibiotics in farmed fish to reduce pathogenic vibrio and its biofilm, which has gradually caused the emergence of vibrio resistance and increased the aquaculture industry’s burden. Nandita et al 2019, found a characteristic lysin in V. parahaemolyticus phage, with lytic activity against various vibrio species, thus expected to become a promising bio-bactericide process for the treatment of vibrio resistance to solve the problem of antibiotics overuse in aquatic industry.…”
Section: Application Of Phage For Prevention and Control Of Biofilmmentioning
confidence: 99%